2019
DOI: 10.1002/term.2900
|View full text |Cite
|
Sign up to set email alerts
|

Urothelial cell senescence is not linked with telomere shortening

Abstract: The success of regenerative medicine relies in part on the quality of the cells implanted. Cell cultures from cells isolated from bladder washes have been successfully established, but molecular changes and cell characteristics have not been explored in detail. In this work, we analysed the role of telomere shortening in relation to the regenerative potential and senescence of cells isolated from bladder washes and expanded in culture. We also analysed whether bladder washes would be a potential source for att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Recently, it has been shown that urothelial senescence increased with age in Wistar urothelium [24]. In addition, cultured urothelial cells can undergo a telomere-shortening-independent senescent phenotype, suggesting that senescence could participle in the aging-related bladder alterations [79]. Mechanistically, aging bladder dysfunction was linked to mitochondrial damage-induced NLRP3/IL-1β inflammasome activation [80].…”
Section: Aging Bladdermentioning
confidence: 99%
“…Recently, it has been shown that urothelial senescence increased with age in Wistar urothelium [24]. In addition, cultured urothelial cells can undergo a telomere-shortening-independent senescent phenotype, suggesting that senescence could participle in the aging-related bladder alterations [79]. Mechanistically, aging bladder dysfunction was linked to mitochondrial damage-induced NLRP3/IL-1β inflammasome activation [80].…”
Section: Aging Bladdermentioning
confidence: 99%